Miliary tuberculosis and acquired immunodeficiency syndrome - 'a cursed duet' - Atif Tatari; Sahana Ramanujam; Suja Mathai; Nigahus Karabulut; Robert L. Moser; Sara L. Wallach (Greater Baltimore Medical Center, 2016)
Tuberculous osteomyelitis is rare and usually involves the vertebrae but is seldom found in the foot. The uncommon site and ability to mimic other disorders clinically and radiographically leads to diagnostic and therapeutic delays. We report a case of a 40-year-old man who initially presented to his podiatrist with intermittent pain and swelling of his right ankle and foot that lasted for a year. He also started to exhibit significant weight loss and unexplained fevers and was subsequently hospitalized for cellulitis of his right foot. On further workup, patient was found to have miliary tuberculosis (TB) and acquired immunodeficiency syndrome (AIDS). Patient was treated with anti-TB therapy for 9 months and highly active anti-retroviral therapy. Our patient presented with ongoing chronic right foot and ankle pain that was proven to be secondary to TB osteomyelitis of cuneiform bones of the right ankle in the setting of AIDS. The patient's clinical presentation was unusual due to symptom duration and lack of systemic characteristics. Like our case, reported incidence of osteomyelitis of bone/joint in extrapulmonary TB is estimated to be 10%, and out of all bones/joint TB cases, only 1% are found to be in the foot.